PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM MENANGANI KRISIS BENCANA PENGUNGSI ROHINGYA DI BANGLADESH TAHUN 2018-2019 - Mutiarani Ernanda; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The humanitarian crisis is experienced by hundreds of thousands of Rohingya living in Myanmar because of discrimination by the people and the government of the country which does not recognize the existence of the Rohingya as part of Myanmar, causing the Rohingyas to flee from Myanmar to seek protection and better life and the peak occurred in August 2017. Hundreds of thousands of Rohingya fled to nearby countries, one of them is Bangladesh. The influx of ethnic Rohingya into Bangladesh in a very large wave raises concerns for the Bangladeshi government about the risk of crisis that may be caused by these conditions, especially when Bangladesh begins to enter the Monsoon which every year becomes a concern for Bangladesh due to impact it has on the local community. This study uses a Pluralism perspective which believes that state is not the only actor in International Relations and is guided by the International Organization theory which explains that International Organization have an important role in international. The method used a qualitative method with data collection techniques through the official website www.iombangladesh.com and library research from several journals, books and theses. This study shows the role of International organization for Migration (IOM) in Bangladesh in handling Rohingya refugees in 2018-2019. The role by IOM is to provide humanitarian assistance through Shelters / Non-Food Items (NFI), WASH (Water, Sanitation and Hygiene), the provision of health services and disaster management through Site Management and Site Development (SMSD). Keywords: International Organization for Migartion (IOM), Rohingya Refugees, Humanitarian Aid.